LDL particle size distribution is associated with carotid intima-media thickness in healthy 50-year-old men. - Skoglund-Andersson, C; Tang, R; Bond, MG; de Faire, U; Hamsten, A; Karpe, F (1999)
Results of cross-sectional and prospective studies have suggested that small, dense low-density lipoprotein (LDL) particles predispose to coronary heart disease. We investigated the relationships between plasma concentrations of LDL subfractions and intima-media thickness (IMT) of the common carotid artery (CCA), quantified by B-mode ultrasound, in 94 healthy, 50-year-old men, all of whom were homozygous for the apolipoprotein E3 allele. A novel 3% to 7.5% polyacrylamide gradient gel was developed to provide separation of LDL subfractions with high resolution, as was a procedure to quantify plasma concentrations of these LDL subspecies. The LDL particle size distribution pattern obtained by the gradient gel electrophoresis procedure was in good agreement with the one obtained by a well-established, single-spin density gradient ultracentrifugation technique. LDL-II (particle size, 23.5 to 25.0 nm) was the most abundant subfraction, and its plasma concentration correlated closely with the total LDL cholesterol concentration (r=0. 61, P<0.001) but not with CCA IMT (r=-0.13, NS). In contrast, the plasma concentration of the predominant small, dense LDL particle subfraction (LDL-III; particle size, 22.5 to 23.5 nm) correlated strongly with CCA IMT (r=0.42, P<0.001). In multivariate analysis, the plasma concentration of the LDL-III subfraction contributed significantly to the variation in CCA IMT (R(2)=0.19). When plasma triglycerides and LDL cholesterol were forced into the multivariate model, 10% of the variation in CCA IMT was still accounted for by the LDL-III subfraction. In summary, use of a novel and sensitive gradient gel electrophoresis method for evaluation of LDL heterogeneity provided the basis for demonstrating an independent relation between the plasma concentration of small LDL and IMT of the CCA in healthy, middle-aged men.